THE CONCEPT OF A LIFECYCLE SYSTEM FOR ORGANIZING AND MANAGING A MASS SPORTS AND RECREATIONAL PROCESS - Akhmatov M. (Western European Studies, 2025)
This article considers a new life-cyclic approach as a promising strategy for organising and managing mass sports and recreational process on a national scale. The concept as well as the principles of organising a holistic life-cyclic continuous system, consistently covering all age social groups of the population, are proposed
Keywords: сoncept; approach; mass sport; principle